Torsional Strength Prediction of RC Hybrid Deep T-Beam with an Opening using Softened Truss Model - Lisantono, A.; Besari, M.; Suhud, R. (Institute of Research and Community Outreach - Petra Christian University, 2013)
This paper presents an analytical study to predict the torsional behavior of reinforced concrete (RC) hybrid deep T-beam with opening and to compare to the experimental results. The RC hybrid deep T-beam was cast with normal weight concrete web and light weight concrete flanges. Based on the Softened Truss Model and Bredt’s theory, a new equation was derived and proposed to show the relationship between compression strut of light weight concrete and normal weight concrete. Based on the experimental results of cracking angles and curvature equation of light weight concrete and normal weight concrete, a new equation was also proposed to show the relationship between strain diagram of light weight concrete and normal weight concrete. The analytical results show that the prediction of maximum torque capacity of the beams are close to the experimental results, except the prediction of twist angle which are larger than the experimental results.